Double Exchange Model in Triangular Lattice Studied by Truncated Polynomial Expansion Method (Communications in Computational Physics, 2011)
The low temperature properties of double exchange model in triangularlattice are investigated via truncated polynomial expansion method (TPEM), whichreduces the computational complexity and enables parallel computation. We foundthat for the half-filling case a stable 120◦spin configuration phase occurs owing to thefrustration of triangular lattice and is further stabilized by antiferromagnetic (AF) superexchangeinteraction, while a transition between a stable ferromagnetic (FM) phaseand a unique flux phase with small finite-size effect is induced by AF superexchangeinteraction for the quarter-filling case.